The Effect Of Time Differences On Polyacrilamide Gel Electrophoresis On Cassava DNA - Nur Ayu Ramadanti; Dwi Hilda Putri (UNIVERSITAS NEGERI PADANG, 2019)
DNA bands formed from the results of electrophoresis with Polyacrilamide gel are considered as 1 character representing 1 allele. PCR products produce multiple bands (multy bands), which indicates that there are multi alleles in the sample. Electrophoresis is a chemical analysis method based on the movement of charged protein molecules in the electric field. Separation is carried out based on differences in the size of the molecular weight and the electric charge contained by the macro-molecule. In addition, the effect of gel concentratio n, buffer and electrophoresis time also has a role in the results of electrophoresis. This study was conducted to compare the best separation time for acrilamide gel electrophoresis with the results of cassava DNA amplification. The materials used in this study are two cassava varieties, namely: Adira IV 1, Adira IV 2, Adira IV 3, Carvita 25 1, Carvita 25 2, and Carvita 25 3. Using electrophoresis by poly-acrilamide gel with two different time effects: 1 hour 30 minutes and 3 hours. The results of electrophoresis with 3 hours gave better results of DNA visualization compared to 1 hour 30 minutes.